Effect of Milk on the Pharmacokinetics of Oseltamivir in Healthy Volunteers - Morimoto, Kaori; Kishimura, Kozue; Nagami, Takaaki; Kodama, Nao; Ogama, Yoichiro; Yokoyama, Midori; Toda, Shinya; Chiyoda, Takeshi; Shimada, Rieko; Inano, Akihiro; Kano, Takashi; Tamai, Ikumi; et al. (Journal of pharmaceutical sciences, 2011)
We previously showed that oseltamivir, a prodrug of the influenza virus neuraminidase inhibitor Ro 64-0802, is a substrate of proton-coupled oligopeptide transporter (PEPT1), and its intestinal absorption in rats is markedly inhibited by administration with milk. To investigate the importance of PEPT1 for oseltamivir absorption in humans, and the characteristics of the drug–milk interaction, a crossover clinical study was conducted in healthy volunteers, who received 75mg of oseltamivir with 400mL of water or milk. Milk significantly reduced the maximum plasma concentration (Cmax) and the area under the plasma concentration–time curve from 0 to 2h (AUC0–2) of both oseltamivir and Ro 64-0802 (oseltamivir, 68.9% and 34.5%; Ro 64-0802, 69.5% and 14.2%, respectively, vs. water), but had no significant effect on the apparent terminal half-life (t1/2) or AUC0–∞. Urinary recovery of oseltamivir and Ro 64-0802 was significantly reduced to 77.5% of the control by milk. The early reduction of oseltamivir absorption might be through the PEPT1 inhibition by milk peptides. However, the extent of interaction in humans was limited as compared with that in rats, possibly because of species difference in the PEPT1 expression and its contribution. This might be the first report suggesting the clinical drug–food interaction via PEPT1. © 2011 Wiley-Liss, Inc. and the American Pharmacists Association J Pharm Sci 100:3854–3861, 2011